2012
DOI: 10.3171/2012.3.jns111649
|View full text |Cite
|
Sign up to set email alerts
|

Long-term natural history of neurofibromatosis Type 2–associated intracranial tumors

Abstract: Object Neurofibromatosis Type 2 (NF2) is a heritable tumor predisposition syndrome that leads to the development of multiple intracranial tumors, including meningiomas and schwannomas. Because the natural history of these tumors has not been determined, their optimal management has not been established. To define the natural history of NF2-associated intracranial tumors and to optimize management strategies, the authors evaluated long-term clinical and radiographic data in patients with NF2. Methods Consecut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 37 publications
(54 reference statements)
4
82
0
4
Order By: Relevance
“…According to the results of this study, the use of the ABC/2 formula should be limited to non-skull base meningiomas with regular and round or ellipsoid shapes. To obtain a more accurate tumor volume using the ABC/2 formula, Dirks et al have recommended using the ABC/2 formula by dividing the tumor into compartments for multilobulated tumors (2). Although the ABC/2 formula appears to be useful for calculating the growth rate of a tumor rather than quantification of tumor volume, this has been reported as an underestimation (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the results of this study, the use of the ABC/2 formula should be limited to non-skull base meningiomas with regular and round or ellipsoid shapes. To obtain a more accurate tumor volume using the ABC/2 formula, Dirks et al have recommended using the ABC/2 formula by dividing the tumor into compartments for multilobulated tumors (2). Although the ABC/2 formula appears to be useful for calculating the growth rate of a tumor rather than quantification of tumor volume, this has been reported as an underestimation (1).…”
Section: Discussionmentioning
confidence: 99%
“…The ABC/2 formula is frequently used to calculate the volume of intracerebral hemorrhage (ICH) because of its simplicity and quickness; however, the accuracy of the ABC/2 formula has been previously debated (20)(21)(22)(23)(24). Although some studies have used the ABC/2 formula (2,25,26) or the original ellipsoid volume (10,19,27) to measure the volume of intracranial tumors, including meningiomas, few studies have evaluated the accuracy of ABC/2 formula for intracranial tumors. The planimetry method presents a more approximate volume for the real tumor and has been applied in many studies (3,4,(11)(12)(13)(14)(15); however, this method is more cumbersome than the ABC/2 method.…”
Section: Introductionmentioning
confidence: 99%
“…Upon reintroduction of everolimus, VS stabilization was immediately resumed, indicating that inhibition of mTORC1 had a direct inhibitory effect on VS growth, which therefore cannot be ascribed to a ''saltatory'' VS progression pattern. A saltatory growth pattern was described in a single retrospective analysis of digitized MRI films and has never been reported in any other VS natural history series [29]. Based on our observation, we do not recommend stopping everolimus treatment when it led a stabilization of growing VS.…”
Section: Tumor Tissue Biomarker Evaluationmentioning
confidence: 80%
“…1,5,10,18,21 Our study showed 0.33 cm 3 /year of actuarial growth rate, suggesting a slow natural course of VS in children. Our study suggests that the natural growth rate may be slow only in children.…”
Section: Vestibular Schwannoma In Children With Nf2mentioning
confidence: 99%
“…Moreover, tumor growth on follow-up examination in the absence of symptoms or signs is not by itself an indication for surgery because the majority of NF2-associated tumors will enlarge for a certain period of time and then have prolonged silent periods of inactivity while the patient remains asymptomatic. 10 In general, neurological deterioration or cosmetic reasons are the indications for surgery in patients with NF2.…”
Section: Treatment For Children With Nf2mentioning
confidence: 99%